Tracing The Shifting Goals and Curriculum Trends in English Language Teaching (2015-2025): A Systematic Literature Review and Bibliometric Analysis - Puspitaningsih, Indah; Maula Jasmine, Shyifa; Fuadiyah, Fia; Suhartono, Anugrah; Chelsea Kimberly, Abigael; Rosalina, Utami (Sinergi International Journal of Education, 2025)
This study conducts a systematic literature review and bibliometric analysis to investigate the shifting goals and curriculum trends in English Language Teaching (ELT) from 2015 to 2025. Drawing upon a dataset of 92 articles retrieved from the Scopus database, the study identifies influential themes, key authors, dominant approaches, and emerging conceptual developments in the field. The findings reveal a major shift from traditional grammar-based instruction to communicative, reflective, and context-responsive teaching methodologies. Five primary thematic clusters are identified: instructional innovation, intercultural communication, sustainable integration, affective and psychological dimensions, and institutional reform. Furthermore, the study underscores the increasing significance of teacher professionalism, learner autonomy, and interdisciplinary approaches in shaping modern ELT curricula. Data visualization was carried out using VOSviewer, and the review process adhered to PRISMA standards to ensure methodological transparency and rigor. This comprehensive analysis offers valuable insights into how ELT has evolved in response to global educational demands and 21st-century challenges. It provides a strategic foundation for future research, curriculum development, and pedagogical innovation within the dynamic landscape of language education.